Application of the Principle of Separate Legal Entity in relation to the Responsibility of the Beneficial Owner for Unlawful Acts Committed by a Limited Liability Company - Muhammad Raihan Putra Setiawan; Hufron (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
The purpose of this study is to find out how to apply the principle of separation of legal entities (separate legal entity) in relation to the responsibility of beneficial owners for unlawful acts committed by limited liability companies. This research employs a normative juridical method, utilizing both a statutory approach and a conceptual approach. Beneficial owners who use a LLC as a tool to carry out illegal activities or harm other parties have caused various legal problems. In many cases, beneficial owners use layers of ownership to hide their identities, making it difficult for aggrieved third parties to pursue legal liability. This creates injustice and casts doubt on the principles of accountability and fairness in corporate law. The results of this study show that Beneficial Owners are usually not held personally accountable for the company's actions. However, there are important exceptions to this principle. One of the exceptions that allows Beneficial Owners to be held accountable is through the doctrine of piercing the corporate veil. This doctrine applies in situations where the separation between the company and its owners (including the Beneficial Owner) is ignored, especially if there is evidence that the company is being used as a tool to commit unlawful or fraudulent acts. If the company is proven to be used for illegal personal gain, such as embezzlement, money laundering, or evading legal obligations, the legal authority may pursue personal liability against the Beneficial Owner.